Determinación de anfetaminas en orina, por el método multidrogas en los estudiantes de bachillerato del Colegio Nacional Adolfo Valarezo de la ciudad de Loja - Collaguazo Torres, Rodrigo Alexander (2014)
The present study aims to determine the presence of amphetamines in urine from Adolfo Valarezo National College baccalaureate students by the multidrug method. This drug is a stimulant substance of the central nervous system that has addictive effects i.e. it induces compulsive consumption; uncontrolled, repeated, increased doses, more frequent and long-term. It's clinical effects depend on the dose and route of administration. Amphetamine, according to a report issued by the United Nations Office on Drugs and Crime in June 2012 , is the second most consumed drug in the world, and in Ecuador ranks third place. The aim of this thesis is to determine the presence of amphetamine in urine by age, schooling, and its relation to the triggers; we used a cross-sectional, descriptive study, for which the study population consisted of the 224 high school students who met the inclusion criteria. For the determination of amphetamines in urine, the multidrug method by immunochromatography was used, which gave no positive results. Finally, to conclude, it is important to note that through the surveys it was obtained that 8% of the students have used drugs at some point in their lives, and did so under the influence of their friends, and 73% of students state they are aware that there are drug addiction in the educational institution. Keywords: amphetamine, multidrug method.